2008
DOI: 10.1136/vr.162.19.618
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cerebrospinal fluid in healthy rabbits and rabbits with clinically suspected encephalitozoonosis

Abstract: Samples of uncontaminated cerebrospinal fluid (csf) were collected from the cisterna magna of 20 healthy laboratory rabbits and 21 pet rabbits with vestibular disease and/or paresis due to clinically suspected encephalitozoonosis. In the healthy rabbits' csf the leucocyte count was Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 15 publications
1
17
1
1
Order By: Relevance
“…It was concluded that lymphomonocytic pleocytosis and increased concentrations of protein in CSF are characteristic signs of encephalitozoonosis in rabbits. However, any other viral, protozoan or immune-mediated encephalitis can induce a similar result (Jass et al 2008). …”
Section: Diagnosic Proceduresmentioning
confidence: 94%
See 2 more Smart Citations
“…It was concluded that lymphomonocytic pleocytosis and increased concentrations of protein in CSF are characteristic signs of encephalitozoonosis in rabbits. However, any other viral, protozoan or immune-mediated encephalitis can induce a similar result (Jass et al 2008). …”
Section: Diagnosic Proceduresmentioning
confidence: 94%
“…A recent study documented that the analysis of cerebrospinal fluid (CSF) can support a clinical diagnosis of encephalitozoonosis in rabbits (Jass et al 2008). It was concluded that lymphomonocytic pleocytosis and increased concentrations of protein in CSF are characteristic signs of encephalitozoonosis in rabbits.…”
Section: Diagnosic Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…This may also be seen with other infections (Jass and others 2008) and is not diagnostic as a single result. However, observed changes increase the likelihood of E cuniculi infection being present.…”
Section: The Grey Areasmentioning
confidence: 97%
“…Even when available, the usefulness of PCR is unclear, since the presence of E. cuniculi DNA in body fl uids does not correlate well with disease. 63,64 Additionally, negative urine results do not exclude encephalitozoonosis because spores may be shed intermittently. 45 Histopathology is a good diagnostic tool for biopsy or postmortem specimens.…”
Section: Encephalitozoon C Uniculimentioning
confidence: 99%